Long Pinions for Alternative Transmission Mechanizations - Raghavan, Madhusudan (Proceedings of Engineering and Technology Innovation, 2018)
Multi-speed transmissions are used in the automotive industry. The design of such transmissions may be framed as an algebraic/graph theory problem. Such an approach is particularly useful for designs with multiple planetary gear sets. Some automotive manufacturers use “long pinions” or “shared pinions” as building block elements within these gear sets. The long pinion is an interesting architectural arrangement that combines certain packaging and functional attributes. In the present article, the algebraic use of the long pinion is demonstrated in the creation of vastly different transmission architectures from the same skeleton diagram.